Józef Kermisz (1907–2005) – twórca badań nad Szoa - David Silberklang (Zagłada Żydów)
Józef Kermisz (1907–2005) was a historian and an archivist who helped lay the foundations for Shoah research in Poland and Israel. In 1944 joined the Central Jewish Historical Commission where became the chief archivist. Since then his life has been devoted to retrieving wartime archival material. As archive director (in the Jewish Historical Institute in Poland and at Yad Vashem in Israel) he sought to develop an archive both for future historical research and for trials of suspected war criminal. He played a major role in discovering and preserving important documentation on the Shoah in Poland. Among his major professional achievements were preparing documentation for the prosecution in the Eichmann trial, and publishing Czerniakow’s diary and the full edition of the underground press of the Warsaw ghetto. He was one of the world’s leading experts on the Ringelblum Archive and other hidden Jewish documentation from the Holocaust. Kermisz left behind a legacy of a vast research infrastructure that he created and that will occupy scholars for generations.